Maximum Oxygen Consumption and Muscle Efficiency in Nonprofessional Youth and Professional Adult Soccer Players - Cofre-Bolados, C (Universidad de Murcia, 2023)
Soccer has been described as a maximal and/or near-maximal effort sport, layered on a low to moderate intensity exercise base. The available evidence suggests that adult male soccer players cover approximate distances of 10 to 12 km during a match and 8.1 km for youth players. The objective of the study is to compare the maximum aerobic power parameters of professional soccer players and youth players. A cross-sectional correlational descriptive study was carried out, 52 adult soccer players and 57 youth soccer players participated. The results reported that the absolute maximum VO2 does not present a significant difference between adults vs juveniles; The relative maximum VO2 in ml/kgmin presents a significant difference in favor of the Juveniles; The maximum aerobic speed in km/h presents a significant difference in favor of the adults and the muscular efficiency in percentage presents a significant difference in favor of the adults. In conclusion, adult professional soccer players have an absolute maximum VO2 similar to youth soccer players; relative oxygen consumption is higher in young soccer players; but the maximum aerobic speed and muscular efficiency are once again higher in adult soccer players. © 2023 Authors. All rights reserved.